Cronkhite-Canada Syndrome: A Case Report and Review of Literature - Kevin T. Kao; Jitesh K. Patel; Vijayamalini Pampati (Gastroenterology Research and Practice)
Cronkhite-Canada syndrome (CCS) is a rare syndrome first described in 1955. (1) Since then, 400 cases worldwide have been reported in the literature. The disease is characterized by diffuse gastrointestinal polyposis, dystrophic changes of the fingernails, alopecia, cutaneous hyperpigmentation, diarrhea, weight loss, and abdominal pain. (2) The etiology is currently unknown, but an autoimmune process is suspected. The workup is based on history and physical followed by imaging and endoscopy with biopsy to confirm gastrointestinal polyposis. The goal of treatment focuses on symptomatic management of the patient and nutritional support.